Accidental Ingestion of a Dental Bur during Endodontic Procedure: A Case Report - Khadka, Sanchita; Koirala, Bandana; Shrestha, Sneha; Birajee, Gajendra (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Accidental ingestion of dental materials and instruments during the routine dental procedures especially in young children can occur at any time. The aim of this case report was to highlight on the recognition and management of such condition immediately for the prevention of any adverse complications. A 3-year-old male child accidentally swallowed a round diamond bur that popped out of the air-rotor handpiece during access cavity preparation on 65. There were no signs of airway obstruction and immediate postero-anterior view of chest and abdomen showed the presence of bur in the gastrointestinal tract which got eliminated in stool on the fourth day, uneventfully.